1996
DOI: 10.1063/1.868801
|View full text |Cite
|
Sign up to set email alerts
|

Control of laminar vortex shedding behind a circular cylinder using splitter plates

Abstract: Laminar vortex shedding behind a circular cylinder and its control using splitter plates attached to the cylinder are simulated. The vortex shedding behind a circular cylinder completely disappears when the length of the splitter plate is larger than a critical length, and this critical length is found to be proportional to the Reynolds number. The Strouhal number of the vortex shedding is rapidly decreasing with the increased plate length until the plate length (l) is nearly the same as the cylinder diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
128
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(147 citation statements)
references
References 29 publications
17
128
0
2
Order By: Relevance
“…[9]). The amplitude of the fluctuations of the lift coefficient is 0.44, which is slightly lower than the value predicted in the past studies (0.52 at Re = 150 in the literature [5]; 0.48 at Re = 140 Kwon and Choi [10]). The time-averaged drag coefficient C D,ave predicted in the present computation is 1.27, which is approximately in good agreement with the value in the literature, C D,ave = 1.34 [5].…”
Section: Governing Equations and Finite Difference Schemementioning
confidence: 38%
“…[9]). The amplitude of the fluctuations of the lift coefficient is 0.44, which is slightly lower than the value predicted in the past studies (0.52 at Re = 150 in the literature [5]; 0.48 at Re = 140 Kwon and Choi [10]). The time-averaged drag coefficient C D,ave predicted in the present computation is 1.27, which is approximately in good agreement with the value in the literature, C D,ave = 1.34 [5].…”
Section: Governing Equations and Finite Difference Schemementioning
confidence: 38%
“…[2]Gerrard [3]investigated the effect of length of splitter plate, attached to the circular cylinder, on the wake flow characteristics. He showed that the Strouhal number decreased when the splitter plate length was smaller than the cylinder diameter, but it increased for 1<L/D<2.Kwon and Choi [4] conducted a numerical study on the control of vortex shedding in laminar flow downstream of the circular cylinder using splitter plates. They pointed out that the vortex shedding downstream of the circular cylinder completely disappears when the length of the splitter plate is longer than a critical length, which is found to be proportional to the Reynold number.Akilli and Rockwell [5] investigated the vortex formation in the junction of the flat plate andcircular cylinder in shallow water flow, using dye visualization and particle image velocimetry (PIV) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Vortex shedding is associated with temporally unstable eigenmodes which are heavily weighted by the near field [263]. Kwon et al [264] used splitter plates to control the laminar vortex shedding behind a circular cylinder. They found that the vortex shedding completely disappeared when the length of the splitter plate is larger than a critical length.…”
Section: Introductionmentioning
confidence: 99%